2009
DOI: 10.1089/thy.2009.0108
|View full text |Cite
|
Sign up to set email alerts
|

Acute Thyroid Hormone Withdrawal in Athyreotic Patients Results in a State of Insulin Resistance

Abstract: It is well known that thyroid hormones are important regulators of energy balance and intermediate metabolism. With regard to glucose homeostasis, hyperthyroidism is associated with a state of insulin resistance due to increased hepatic gluconeogenesis (1). In hypothyroidism however, despite the fact that hepatic gluconeogensis has been described as unchanged (2) or decreased (3,4), experiments in animal models have demonstrated a state of insulin resistance both in the adipocyte and in the skeletal muscle (5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 32 publications
3
32
0
4
Order By: Relevance
“…In fact, Figure 5 shows in Tx rats a reduced amount of GLUT4 on skeletal muscle and a decreased response to insulin stimulus, findings that have been reported in animal models (42,43) and hypothyroid patients (44,45). It also shows a reestablishment of the insulin response, in rats under 5-day T 3 treatment, a procedure that increased the GLUT4 content, as described (5,27).…”
Section: Brunetto Et Alsupporting
confidence: 71%
“…In fact, Figure 5 shows in Tx rats a reduced amount of GLUT4 on skeletal muscle and a decreased response to insulin stimulus, findings that have been reported in animal models (42,43) and hypothyroid patients (44,45). It also shows a reestablishment of the insulin response, in rats under 5-day T 3 treatment, a procedure that increased the GLUT4 content, as described (5,27).…”
Section: Brunetto Et Alsupporting
confidence: 71%
“…Among the above-mentioned symptomatology, insulin resistance has been the most important facet connecting thyroid dysfunction and T2DM. Insulin resistance is a condition which occurs in both hypothyroidism and hyperthyroidism [27]. …”
Section: Relation Between the Pathological Features Exhibited In Hmentioning
confidence: 99%
“…Hyperthyroidism has been associated with insulin resistance which has been linked with elevated glucose turnover, increased intestinal glucose absorption, elevated hepatic glucose output, increased free fatty acid concentrations, increased fasting and or postprandial insulin an proinsulin levels, and increased peripheral glucose transport accompanied by glucose utilization [27, 34]. T2DM patients with thyroid dysfunction have been proven to be more susceptible to ketosis [35] and ketogenesis [36].…”
Section: Relation Between the Pathological Features Exhibited In Hmentioning
confidence: 99%
“…This may be an alternative mechanism explaining the effect of hypothyreosis on decreasing glucose utilisation by peripheral cells [8]. Brenta et al observed that patients with hypothyroidism, compared to euthyreotic subjects, demonstrated a significantly lower glucose utilisation during a short intravenous insulin tolerance test [28].…”
Section: Hypothyroidismmentioning
confidence: 99%